2019
DOI: 10.1016/j.clim.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant natural killer (NK) cell activation and dysfunction among ART-treated HIV-infected adults in an African cohort

Abstract: Background We examined NK cell phenotypes and functions after seven years of ART and undetectable viral loads (<50 copies/ml) with restored CD4 T-cell counts (≥500 cells/μl) and age-matched healthy-HIV-uninfected individuals from the same community. Methods Using flow-cytometry, NK cell phenotypes were described using lineage markers (CD56 +/- CD16 +/− ). NK cell activation was determined by expression of activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 34 publications
7
28
0
Order By: Relevance
“…Unfortunately, both T and NK cells’ effector responses often become dysfunctional upon HIV infection ( 22 , 23 ), and do not completely recover even after ART treatment ( 24 , 25 ), which historically has been initiated during the chronic phase of infection. However, there exists rare PLWH that can naturally control HIV in the absence of ART through immune-mediated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, both T and NK cells’ effector responses often become dysfunctional upon HIV infection ( 22 , 23 ), and do not completely recover even after ART treatment ( 24 , 25 ), which historically has been initiated during the chronic phase of infection. However, there exists rare PLWH that can naturally control HIV in the absence of ART through immune-mediated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The ADCC involves both the antibodies and effector cells like NK cells. It is known that HIV-infected individuals are known to have compromised NK cell function ( 45 ). Although ADCC antibodies can effectively identify HIV-1-infected cells, the NK cells in these patients may not be able to lyse the reactivated reservoir ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…NKG2D is an activating receptor that binds to the surface ligand NKG2DL to mediate the killing function of NK cells. Numerous studies have reported a general decrease in NKG2D expression in HIV-infected individuals ( 21 , 60 ). In addition, NKG2D expression is negatively correlated with viral set point ( 56 ), and the capacity of NK cells to kill target cells decreases with decreased NKG2D ( 61 ).…”
Section: Nk Cell Dysfunction During Hiv Infectionmentioning
confidence: 99%